2013
DOI: 10.1021/ja4074744
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Collapse of Foldamer Capsules Drives Picomolar-Level Chloride Binding in Aqueous Acetonitrile Solutions

Abstract: Aqueous media are competitive environments in which to perform host−guest chemistry, particularly when the guest is highly charged. While hydrophobic binding is a recognized approach to this challenge in which apolar pockets can be designed to recognize apolar guests in water, complementary strategies are required for hydrophilic anions like chloride. Here, we present evidence of such an alternative mechanism, used everyday by proteins yet rare for artificial receptors, wherein hydrophobic interactions are sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 98 publications
4
135
0
Order By: Relevance
“…The combination of C−H hydrogen bonding and the hydrophobic effect has also been elegantly used by Flood and co‐workers for the recognition of chloride anions by the aryl‐triazole foldamer 18 in organic–aqueous solution (Figure 6 a) 104. Hydrophobic interactions are responsible for organizing and stabilizing the foldamer, which forms a 2:1 stoichiometric complex with chloride in 1:1 CH 3 CN/H 2 O solution, with about 80 % of the hydrophobic π surfaces buried within the duplex in the process.…”
Section: Small‐molecule Supramolecular Anion Receptorsmentioning
confidence: 99%
“…The combination of C−H hydrogen bonding and the hydrophobic effect has also been elegantly used by Flood and co‐workers for the recognition of chloride anions by the aryl‐triazole foldamer 18 in organic–aqueous solution (Figure 6 a) 104. Hydrophobic interactions are responsible for organizing and stabilizing the foldamer, which forms a 2:1 stoichiometric complex with chloride in 1:1 CH 3 CN/H 2 O solution, with about 80 % of the hydrophobic π surfaces buried within the duplex in the process.…”
Section: Small‐molecule Supramolecular Anion Receptorsmentioning
confidence: 99%
“…Foldamers are one potential solution, and progress has been made in a few instances towards protein-like functionality. 47,48 Regarding host design, three points that the workshop frequently returned to are detailed below.…”
Section: [Insert Figure 2]mentioning
confidence: 99%
“…Although examples of binding apolar guests in water on the basis of hydrophobic interactions are well known, Hua et al 23 demonstrated in a seminal report that hydrophobic interactions can be exploited to drive the binding of hydrophilic anions in aqueous solutions. The two aryl-triazole foldamers 49 and 50 ( Figure 16) were studied, in which the main chain could associate intramolecularly or intermolecularly via p-stacking, and the azobenzene unit further shielded the anion-binding site from solvents.…”
Section: Ch Hydrogen-bond-based Receptorsmentioning
confidence: 99%